More from less: Genome skimming for nuclear markers for animal phylogenomics, a case study using decapod crustaceans. Issue 2 (23rd April 2021) - Tan, Mun Hua; Gan, Han Ming; Bracken-Grissom, Heather; Chan, Tin-Yam; Grandjean, Frederic; Austin, Christopher M
Abstract: Low coverage genome sequencing is rapid and cost-effective for recovering complete mitochondrial genomes for crustacean phylogenomics. The recovery of high-copy-number nuclear genes, including histone H3, 18S and 28S ribosomal RNAs, is also possible using this approach based on our research with freshwater crayfishes (Astacidea). We explored the potential of genome skimming (GS) to recover additional nuclear genes from shallow sequencing projects using decapod crustaceans. Using an in silico -baited approach, we recovered three additional core histone genes (H2A, H2B, and H4) from our low-coverage decapod dataset (99 species, 69 genera, 38 families, 10 infraorders). Phylogenetic analyses using various combinations of mitochondrial and nuclear genes for the entire decapod dataset and a subset of 40 species of crayfishes showed that the evolutionary rates for different classes of genes varied widely. A very high level of congruence was nevertheless found between trees from the six nuclear genes and those derived from the mitogenome sequences for freshwater crayfish. These findings indicate that nuclear genes recovered from the same genome skimming datasets designed to obtain mitogenomes can be used to support more robust and comprehensive phylogenetic analyses. Further, a search for additional intron-less nuclear genes identified several high-copy-number genes across the decapod dataset, and recovery of NaK, PEPCK, and GAPDH gene fragments is possible at slightly elevated coverage, suggesting the potential and utility of GS in recovering even more nuclear genetic information for phylogenetic studies from these inexpensive and increasingly abundant datasets.